(untitled) (Vietnam Journal of Community Medicine, 2024)
Background and purpose: Sports injuries involving the anterior cruciate ligament (ACL) are among the most common. Anterior Cruciate Ligament Reconstruction (ACLR) techniques have continuously improved since the 1980s. While ACLR has become increasingly reliable in recent years, rotational instability of the knee has yet to be completely restored. It is also important to note that the graft failure rate remains high (17.1%-18%), the return to pre-injury sports activity rate is low (44%-72%), and anterolateral rotational instability remains a problem for approximately 25% to 30% of patients after surgery. It is an advanced surgical procedure used to treat rotational instabilities known as Lemaire lateral extra-articular tenodesis augmentation (LET). It is used as an adjunct to ACLR and improves knee rotational instability. Young patients with anterolateral rotational instability after ACL rupture can benefit from this procedure as it allows them to resume sports activities following the reconstruction of the ACL. Method: During the period October 2022 to Ferbuary 2024, 53 patients under the age of 25 with ruptured anterior cruciate ligaments (ACL) with a Pivot shift test result indicating a grade 2-3 underwent ACL reconstruction utilizing autologous superficial Quadriceps tendon autograft along with the modified Lemaire lateral extra-articular tenodesis augmentation (LET). The International Knee Documentation Committee (IKDC) score, the Tegner Activity Scale (TAS), and the Lysholm score were assessed before and after surgery. The KT-1000 arthrometer and Pivot shift test were used to evaluate joint laxity. Results: In a minimum follow-up period of one year, 53 patients between the ages of 18 and 25 (mean 22.4 ± 3.8 years) were included. Six of the patients lost contact with us during follow-up. In the study, all patients (N = 53; 30 men and 23 women) had ACL grafts were fixed by all – inside technique. During the 10th month, the ACL re-tear rate is 1.9% (one case). At the final follow-up (mean 13.1 ± 2.1 months), the mean IKDC score was 88.9 ± 8.9, the mean Lysholm score was 93.8 ± 5.9, and the mean Tegner score was The average was 6.4 ± 1.5. Conclusion: In young patients with high rotational instability after ACL rupture, LET and ACLR have demonstrated favorable clinical outcomes. A complete return to sports activities was possible for all patients without any complications.